On Interpolation Sequences of One Class of Functions Analytic in the Unit Disk - Vynnyts’kyi, B. V.; Sheparovych, I. B. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish a criterion for the existence of a solution of the interpolation problem f(λ n ) = b n in the class of functions f analytic in the unit disk and satisfying the relation ( τ _1 ( 0;1 ) ) ( c_1 >0 ) ( z,| z | < 1 ): | f( z ) | ( c_1 γ ^τ _1 ( c_1 1 - | z | ) ), where γ: [1; +∞) → (0; +∞) is an increasing function such that the function lnγ(t) is convex with respect to lnt on the interval [1; +∞) and lnt = o(lnγ(t)), t → ∞.